2021
DOI: 10.3389/fvets.2021.771341
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Flow Immunoassay for Visible Detection of Human Brucellosis Based on Blue Silica Nanoparticles

Abstract: Brucellosis is a highly contagious zoonosis chronic infectious disease with a strong latent capability to endanger human health and economic development via direct or indirect ways. However, the existing methods for brucellosis diagnosis are time-consuming and expensive as they require a tedious experimental procedure and a sophisticated experimental device and performance. To overcome these defects, it is truly necessary to establish a real-time, on-site, and rapid detection method for human brucellosis. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This study indicates that LFIA can be used as a substitution screening test for brucellosis. The developed LFA strips could detect the Ab against Brucella in a serum sample at a minimal concentration relative to the Rose Bengal test, where the minimal amount of Ab against Brucella in the serum sample detected was 1.51.58 and 1.86 S/P in the LFA strips and Rose Bengal test, respectively; these lower cutoff values indicate a high sensitivity, which is one of the most important features of a good test [24]. In other studies on the detection of Corynebacterium pseudotuberculosis, the minimal concentration that gave positive results in LFIT was CFU/0.1 mL [25], while for, Staphylococcus aureus, the sensitivity was 106 CFU/0.1 mL [26].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that LFIA can be used as a substitution screening test for brucellosis. The developed LFA strips could detect the Ab against Brucella in a serum sample at a minimal concentration relative to the Rose Bengal test, where the minimal amount of Ab against Brucella in the serum sample detected was 1.51.58 and 1.86 S/P in the LFA strips and Rose Bengal test, respectively; these lower cutoff values indicate a high sensitivity, which is one of the most important features of a good test [24]. In other studies on the detection of Corynebacterium pseudotuberculosis, the minimal concentration that gave positive results in LFIT was CFU/0.1 mL [25], while for, Staphylococcus aureus, the sensitivity was 106 CFU/0.1 mL [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Si nanoparticles have been used for the development of a LFIA test for the detection of human brucellosis. The Si NPs were modified using 3-aminopropyl triethoxysilane (APTES), for the covalent binding of Staphylococcal protein A (SPA), after the activation with glutaraldehyde ( Ge et al, 2021 ). In another recent study, a rapid test for the detection of the prostate specific antigen (PSA) was developed using silver assembled silica nanoparticles.…”
Section: Functionalization Methodsmentioning
confidence: 99%
“…Due to these properties, they have the potential to become a detection label with applications in LFIA. Lirui Ge et al (2021) reported the first use of silica nanoparticles in LFIA, achieving a detection limit of 10–5 (0.01 IU/ml) for Brucella spp. antibody detection.…”
Section: Detection Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocking was carried out by adding polyethene glycol (PEG-20,000) 1% m/v final concentration with gentle stirring for another 15 min, followed by centrifugation at 12,000 rpm for one hour. The conjugated nanogold particles were suspended in 1 mL dilution buffer containing (sucrose3% (w/v), 20 mM Tris, bovine serum albumin 1% (w/v), and sodium azide 0.02% (w/v)) and stored at 4 °C [ 18 ].…”
Section: Methodsmentioning
confidence: 99%